2010
DOI: 10.1186/1742-2094-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets in neuroinflammation: a wide-angle perspective

Abstract: ObjectivesThis review summarizes recent developments in platelet biology relevant to neuroinflammatory disorders. Multiple sclerosis (MS) is taken as the "Poster Child" of these disorders but the implications are wide. The role of platelets in inflammation is well appreciated in the cardiovascular and cancer research communities but appears to be relatively neglected in neurological research.OrganizationAfter a brief introduction to platelets, topics covered include the matrix metalloproteinases, platelet chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 302 publications
(324 reference statements)
0
93
0
2
Order By: Relevance
“…We further demonstrated that altered platelets have a remarkable ability to damage and cross the blood brain barrier [20]. This is not unexpected, since platelets are the source of multiple pro-inflammatory substances, including TNF, IL-6 and CD40, which are known for altering the BBB [18][19][20][21][22][23]. Besides their role in pathogenesis, platelets might also play a key role in the regulation of brain function.…”
Section: Platelets Role In the Central Nervous Systemmentioning
confidence: 88%
See 3 more Smart Citations
“…We further demonstrated that altered platelets have a remarkable ability to damage and cross the blood brain barrier [20]. This is not unexpected, since platelets are the source of multiple pro-inflammatory substances, including TNF, IL-6 and CD40, which are known for altering the BBB [18][19][20][21][22][23]. Besides their role in pathogenesis, platelets might also play a key role in the regulation of brain function.…”
Section: Platelets Role In the Central Nervous Systemmentioning
confidence: 88%
“…Interrogation of an arrayed cDNA library proved that platelets contain many cytokine messenger RNAs [9][10][11]. Second, platelets have been shown to express chemokine receptors, such as MIP-1α, PDGF, and RANTES (the Macrophage Inflammatory Protein, the Platelet derived growth factor and the Regulated on Activation, Normal T Cell Expressed and Secreted) that trigger the chemotaxis of other cells to the sites of inflammation [9][10][11]18].…”
Section: Platelets and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…A review investigating the role of thrombocytes in neuroinflammation pointed out that the thrombocytes play major roles in inflammation and immunity. 23 According to Gasparyan et al, 24 MPV value is a parameter that varies according to proinflammatory and prothrombotic conditions. Elevated MPV was indicated as an independent risk factor for myocardial infarction and CVE, while a low MPV value was shown to be associated with the activity of inflammatory rheumatologic diseases.…”
Section: Discussionmentioning
confidence: 99%